PENGARUH METODE LATIHAN “DRILL SPIKE” TERHADAP KETEPATAN SPIKE SISWA AKADEMI BOLA VOLI BULELENG - I Wayan Surya Prama Teguh Ananta; Made Agus Dharmadi; I Kadek Happy Kardiawan (Berajah Journal, 2026)
This study aimed to analyze the effect of the drill spike training method on the spike accuracy of students at the Buleleng Volleyball Academy. The research employed an experimental method using a Two Groups Pretest–Posttest Design involving male athletes as the research subjects. The experimental group received structured and repetitive drill spike training for 12 sessions, while the control group underwent the academy’s regular training program. The results showed a greater improvement in spike accuracy in the experimental group compared to the control group. The average posttest score of the experimental group increased from 20.00 to 38.10, whereas the control group improved from 23.10 to 32.50. The results of the Independent Sample t-test indicated a significance value of 0.000 < 0.05, demonstrating that the drill spike training method had a significant effect on improving spike accuracy. The improvement occurred because the training was conducted repeatedly, systematically, and focused on movement coordination, timing, strength, and ball direction control. In addition to enhancing technical skills, this method also helped improve athletes’ confidence and consistency during attacks. Therefore, the drill spike training method can be used as an effective alternative training approach to improve spike accuracy in volleyball.